Elderly victims of violence: family assessment through the Calgary model - Alarcon, Miriam Fernanda Sanches [UNESP]; Cardoso, Bruna Carvalho; Ala, Caroline Borges; Damaceno, Daniela Garcia [UNESP]; Sponchiado, Viviane Boacnin Yoneda; Marin, Maria José Sanches [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: To understand the structure, development, and functionality of the family of the elderly victim of violence. METHOD: Descriptive research with a qualitative approach, based on the Calgary Family Assessment Model. Four elderly people who suffered violence and their family members were assessed at home, from October to November 2019. Data analysis was based on the genogram and ecomap, as proposed in the model. RESULTS: It was found that the members of the four families had low schooling and financial difficulties. As for the social support network, the neighbors, the health unit and the Church stood out. The members of each family nucleus expressed feelings of fear, insecurity, anger, nervousness, sadness and impotence, resulting from the conflict between the couple. FINAL CONSIDERATIONS: In the assessed families, weaknesses and potentialities in the structure, development and functioning are highlighted, which must be considered in the elaboration of the care plan.